The Determinants of Taxpayer Compliance with Tax Socialization as A Moderating Variable in UPPD Samsat Banjarmasin II - Nabila Ahya Syaffitri; Antung Noor Asiah; Sri Ernawati; Saifhul Anuar Syahdan (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyse and provide empirical evidence on the influence of taxpayer awareness, tax sanctions, understanding of e-Samsat, and motor vehicle tax amnesty on taxpayer compliance with tax socialisation, with the moderating variable of tax socialisation at UPPD Samsat Banjarmasin II. The research source is primary data collected through questionnaires. The population in this study was 426,239 two-wheeled and four-wheeled motor vehicle taxpayers. The sampling method used was accidental sampling, and the Slovin formula was used, resulting in 100 motor vehicle taxpayers as the research sample. Data were analysed using multiple linear regression and moderated regression in IBM SPSS Statistics 26. The results showed that taxpayer awareness, tax sanctions, and understanding of e-Samsat had a positive effect on taxpayer compliance. Meanwhile, motor vehicle tax amnesty had no effect on taxpayer compliance. Tax socialisation moderated (strengthened) the influence of taxpayer awareness, tax sanctions, understanding of e-Samsat, and motor vehicle tax amnesty on taxpayer compliance